Official forecasts and management of oil windfalls - Torfinn Harding; Frederick van der Ploeg (Statistics Norway, Research Department, 2012)
Official forecasts for oil revenues and the burden of pensioners are used to estimate forward-looking fiscal policy rules for Norway and compared with permanent-income and bird-in-hand rules. The results suggest that fiscal reactions have been partial forward-looking with respect to the rising pension bill, but backward-looking with respect to oil and gas revenues. Solvency of the government finances might be an issue with the fiscal rules estimated from historical data. Simulation suggests that declining oil and gas revenue and the costs of a rapidly graying population will substantially deteriorate the net government asset position by 2060 unless fiscal policy becomes more prudent or current pension and fiscal reforms are successful.
Keywords: H20; H63; Q33; 330; oil windfalls; official forecasts; forward-looking fiscal policy rules; permanent income hypothesis; graying population; debt sustainability